Composition and thermal properties of starch in flint maize (Zea mays, L.) kernels: location and crop management effects - Actis, Marcos Daniel (2020)
Composition and thermal properties of starch in flint maize (Zea mays, L.) kernels: location andcrop management effectsFlint maize kernels are processed by the dry-milling industry to produce the flaking grits usedthereafter in the corn flakes industry. Flaking-grit yield during milling depends on kernel hardnesswhereas corn flakes production involves starch gelatinization. Starch composition influences bothcharacteristics of maize kernels. The objective of this work was to analyze the effect of differentcrop environments and management practices on starch composition of kernels and its thermalproperties. Two flint maize hybrids (Cóndor and Morgan, 306) were grown at three locations(Balcarce, Pergamino and Paraná, located in a latitudinal transect of 6°) with different plantdensities (7.5 and 9 plants/m2 ), sowing dates (early and late), and fertilizing rates (with andwithout additional N and S-fertilizer near silking) during two growing seasons (2003-2004 and2004-2005). Crop biomass accumulated from silking to physiological maturity was measured andmean kernel weigh was calculated at harvest. Kernel hardness was estimated by mean of the testweight and percent floaters. Amylose and starch concentration in kernels were determined. Starchthermal properties were analyzed by differential scanning calorimetry and endotherm parameterswere calculated. Cropping conditions modified starch composition of kernels. Amylose/starch ratiodecreased as air temperature decreased from the north to the south and by delaying sowing date.Deposition of amylose in the endosperm of the kernels increased as growing conditions for cropgrowth improved during kernel filling. Starch thermal properties were also modified by thesechanges in starch composition. The onset and peak temperatures, gelatinization enthalpy, andpeak height index were positively associated with amylose concentration and amylose/starchratio, whereas the gelatinization temperature range was negatively associated with both kernelattributes. The results reported herein would contribute to foresee the effect of location andagricultural practices on kernel quality of flint maize, and to make appropriated managementadjustments to obtain a product that meets the market needs.